On Silent Laughter: The Political Humour Depicted in Indonesian Cartoons - Danang Satria Nugraha (VELES Voices of English Language Education Society, 2022)
The cartoon is a part of online media which Indonesian speakers pragmatically favor. Besides being entertaining, the cartoon is popular because it probably contains political humour relevant to the socio-pragmatic situation in society. This study specifically aimed at describing the political humour in Indonesian cartoons. The data used were 222 cartoons. The data was downloaded from online-open source media platforms from November 1st, 2021, to January 5th, 2022. All data was collected from the google search engine based on the digital observation techniques proposed by Cordelois (2010). Apart from being based on the theory of visual metaphors, Attardo’s general theory of verbal humor (GTVH) was utilized to analyze data. The results of this study indicated that, in general, political humour is one of the popular domains of the content of cartoons published in Indonesia’s online media. In particular, political humour consists of at least three types, namely political satire, parody, and irony. Of the three types, parody is the most dominant political humour used in Indonesian cartoons.